Dynamic Field Tests of Single Piles - Norazzlina, M.Sa’don; Pender, M.J.; Orense, R.P; Abdul Razak, Abdul Karim (2010)
This paper presents the results of a full-scale field study of single free-head piles embedded in Auckland residual clay. Four hollow steel pipe piles, each with an outside diameter of 273 mm and wall thickness of 9.3 mm were installed at a site in Pinehill, Auckland. A series of dynamic tests ranging from low excitation (using an instrumented impact hammer and a low-mass loading of an eccentric mass shaker) to high dynamically-induced force from the eccentric mass shaker was performed during the spring and early summer after the winter wet weather, so that the soil can be assumed to be saturated to the ground surface. Results from low amplitude dynamic tests indicated a reduction in the natural frequency of the system from 9.6 Hz to 8.2 Hz after experiencing a higher level of forcing amplitude. This reduction in natural frequency demonstrated the non-linear response of the pile-soil system that was caused by the strain softening of the soil and the formation of a gap between the pile shaft and the surrounding soil.